Antinomies of Alignment: Kuwait and the United States. Issue 3 (12th September 2022) - Lawson, Fred H.; Legrenzi, Matteo
Abstract: Kuwait has forged a strong bilateral security alignment with the United States over the past three decades. But it has also pursued foreign policies that run counter to expressed American objectives and priorities in the Gulf and the broader Middle East. Why this happens can best be explained in terms of a combination of shifts in the overt US commitment to the partnership and changes in the level of threat in the region.